Antibacterial Action of Curcumin against Staphylococcus aureus: A Brief Review - Teow , Sin Yeang; Liew, Kitson; Ali, Syed A.; Khoo, Alan Soo Beng; Peh, Suat Cheng (Hindawi Publishing Corporation, 2016)
Curcumin, the major constituent of Curcuma longa L. (Zingiberaceae family) or turmeric, commonly used for cooking in Asian cuisine, is known to possess a broad range of pharmacological properties at relatively nontoxic doses. Curcumin is found to be effective against Staphylococcus aureus (S. aureus). As demonstrated by in vitro experiment, curcumin exerts even more potent effects when used in combination with various other antibacterial agents. Hence, curcumin which is a natural product derived fromplant is believed to have profoundmedicinal benefits and could be potentially developed into a naturally derived antibiotic in the future. However, there are several noteworthy challenges in the development of curcumin as a medicine. S. aureus infections, particularly those caused by themultidrug-resistant strains, have emerged as a global health issue and urgent action is needed.This review focuses on the antibacterial activities of curcumin against both methicillin-sensitive S. aureus (MSSA) and methicillinresistant S. aureus (MRSA). We also attempt to highlight the potential challenges in the effort of developing curcumin into a therapeutic antibacterial agent.